Effectiveness of mycophenolate mofetil as first-line therapy in AQP4-IgG, MOG-IgG, and seronegative neuromyelitis optica spectrum disorders. (September 2017) - Montcuquet, Alexis; Collongues, Nicolas; Papeix, Caroline; Zephir, Helene; Audoin, Bertrand; Laplaud, David; Bourre, Bertrand; Brochet, Bruno; Camdessanche, Jean-Philippe; Labauge, Pierre; Moreau, Thibault; Brassat, David; et al.
Objective: To evaluate the effectiveness and tolerance of mycophenolate mofetil (MMF) as a first-line treatment in neuromyelitis optica spectrum disorder (NMOSD). Methods: In all, 67 NMOSD patients treated by MMF as first-line therapy, from the NOMADMUS cohort were included. A total of 65 fulfilled 2015 NMOSD criteria, and 5 were myelin oligodendrocyte glycoprotein (MOG)-immunoglobulin G (IgG) positive. Effectiveness was evaluated on percentage of patients continuing MMF, percentage of patients free of relapse, pre- and post-treatment change in the annualized relapse rate (ARR), and Expanded Disability Status Scale (EDSS). Results: Among 67 patients, 40 (59.7%) continued treatment till last follow-up. A total of 33 (49.3%) were relapse-free. The median ARR decreased from one pre-treatment to zero post-treatment. Of 53 patients with complete EDSS data, the score improved or stabilized in 44 (83%; p  < 0.05). Effectiveness was observed in aquaporin-4 (AQP4)-IgG (57.8% continued treatment, 46.7% relapse-free), MOG-IgG (3/5 continued treatment, 4/5 relapse-free), and seronegative NMOSD (64.7% continued treatment, 61.3% relapse-free). In 16 patients with associated steroids, 13 (81.2%) continued MMF till last follow-up versus 15 of 28 (53.6%) in the non-steroid group. Nine patients discontinued treatment for tolerability purpose. Conclusion: MMF showed effectiveness and good tolerability as a first-line therapy in NMOSD, whatever the AQP4-IgG status. Concomitant use of oral steroids at start could limit the risk of treatment failure.